1989
DOI: 10.1292/jvms1939.51.1137
|View full text |Cite
|
Sign up to set email alerts
|

Immunoperoxidase evaluation of pneumonic lesions in calves naturally infected with Pasteurella haemolytica.

Abstract: Immunoperoxidase technique was applied for pathological study on naturally occurring pneumonic tissues of calves from which Pasteurella haemolytica was isolated. Multifocal necrosis occurred in the lungs of 25 out of 42 calves (59.5%) and P. haemolytica antigen was detected in 22 out of the 25 calves (88.0%). The calves were divided into 3 groups according to the number of P. haemolytica isolated. The positive rate of the bacterial antigen detected by the technique was 66.6% (28/42) on the average, reaching up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0
2

Year Published

1990
1990
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 1 publication
4
18
0
2
Order By: Relevance
“…M. haemolytica was not isolated from 9 IHC positive lungs in which 4 samples had necrotic bronchopneumonia (with strong positive reaction) and the others (with weak positive reaction) had chronic suppurative (3 cases), subacute suppurative and fibrinous bronchopneumonia (1 case each). The identification of B. trehalosi from 2 lungs with necrotic lesions as a specific sign of Mannheimiosis [4,15] , and not the isolation of M. haemolytica, may be explainable with the results of Dassanayake et al [16] . They proved B. trehalosi, due to higher growth rate, inhibits the growth of M. haemolytica in vitro and concluded that if these patterns occur in vivo, they may cause failure to routinely isolate M. haemolytica from pneumonic lungs.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…M. haemolytica was not isolated from 9 IHC positive lungs in which 4 samples had necrotic bronchopneumonia (with strong positive reaction) and the others (with weak positive reaction) had chronic suppurative (3 cases), subacute suppurative and fibrinous bronchopneumonia (1 case each). The identification of B. trehalosi from 2 lungs with necrotic lesions as a specific sign of Mannheimiosis [4,15] , and not the isolation of M. haemolytica, may be explainable with the results of Dassanayake et al [16] . They proved B. trehalosi, due to higher growth rate, inhibits the growth of M. haemolytica in vitro and concluded that if these patterns occur in vivo, they may cause failure to routinely isolate M. haemolytica from pneumonic lungs.…”
Section: Discussionmentioning
confidence: 86%
“…Negative culture results in the weak IHC lungs may be due to the low concentration of bacteria or dead bacteria in the tissues examined [5] . The negative IHC results of two bacteriologically positive lungs may be explained by different sampling location for both methods as well as the focal accumulation of bacteria in the lungs [5,17] .…”
Section: Discussionmentioning
confidence: 99%
“…The clinical features, gross and histologic changes observed in this study were characteristics of haemorrhagic septicaemia. Immunoperoxidase evaluation of pneumonic lesions induced by Pasteurella multocida have been described (Haritani et al, 1989) and have been used to differentiate between pneumonic lesions caused by Pasteurella multocida and/or Mannheimia haemolytica (formerly Pasteurella haemolytica) (Haritani et al, 1990). Pasteurella multocida B:2 has been detected using immunoperoxidase technique in the respiratory tract of goats experimentally exposed intratracheally (Shafarin et al, 2009).…”
Section: Pathology and Immunohistochemical Detectionmentioning
confidence: 99%
“…It is an important disease in tropical regions of the world, especially in African and Asian countries. Conventional methods of identification such as serotyping, biotyping, antibiogram determination and pathogenicity as well as molecular methods and characterization are applied in parallel for rapid epidemiological investigations of HS outbreaks (Shivachandra et al, 2011) Immunoperoxidase has been recognised as an important tool not only to show the presence of antigen and vividly localize bacteria, it is also best at demonstrating antigen in dead solubilized bacteria (Haritani et al, 1989). Immunoperoxidase also has superior advantage of revealing the relationship of the lesions to bacteria distribution in the tissues (Haritani et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation